Teacher’s Strategies to Reduce Peer-Group Bullying for Strengthening Elementary Student’s Mental Health - Dilla Agnes Rica Kusumaningrum; Minsih Minsih (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines how exclusive friendship circles trigger bullying and how teachers respond to strengthen elementary students’ mental health at SD Negeri 2 Giritontro, Wonogiri, Central Java. Using a qualitative case study, data were collected through interviews, observations, and documentation involving teachers, sixth-grade students, and school records. The findings show that bullying occurs in verbal, social, and physical forms. Verbal bullying includes teasing and derogatory naming, social bullying involves exclusion from peer activities, and physical bullying includes pushing, hitting, and hair pulling. These behaviors emerge from dominant peer-group dynamics that create in-group and out-group boundaries. Bullying negatively affects victims’ mental health by reducing confidence, increasing fear, causing social withdrawal, and disrupting learning engagement. Teachers address bullying through preventive, repressive, and curative strategies, including class rules, supervision, immediate reprimands, and emotional support. The study highlights the importance of addressing peer-group dynamics to create a safe, inclusive, and supportive school environment for children and strengthen students’ social development and well-being.